Combine the like terms to create an equivalent expression: {-4p+(-6p)}

Question

Combine the like terms to create an equivalent expression:
{-4p+(-6p)}

in progress 0
Amelia 1 week 2021-09-10T05:49:53+00:00 2 Answers 0

Answers ( )

    0
    2021-09-10T05:50:56+00:00

    Answer and Step-by-step explanation:

    Greetings!

    Let's~answer~your~question!

    The~is~an~easy~equation!~First,~you~remove~parenthesis~then~subtract~6p~\\from-4p:

    =-4p-6p

    =-10p

    -10p~should~be~your~final~answer.

    Hope~this~helps!~Have~a~blessed~day~ahead!

    -Isabelle~Williams

    0
    2021-09-10T05:51:11+00:00

    Answer:

    -4p + (-6p) = -10p

    Step-by-step explanation:

    -4p+(-6p)=(-4+(-6))p=-10p

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )